THE SYNTHESIS OF CONJUGATED IMINE DERIVATIVE COMPOUNDS AS POTENTIAL OLED COMPOUND PRECURSORS - Putra Prajnamitra, Ray
OLED is a kind of semiconductor which utilizes organic compounds as the emissive layer. The OLED technology has been widely applied all over the world due to its various advantages. The organic compounds used for OLED usually posses conjugated double bonds system. In this research, two imine derivative compounds have been successfully synthesized. Compound 1, 2,2'-(1E,1'E)-(1,2-phenylenebis(azan-1-yl-1-ylidene))bis(methan-1-yl-1-ylidene)diphenol, posseses imine and phenol groups. The synthesis of this compound was done using salicylaldehyde and 1,2-diaminobenzene. The crystal of compound 1 is yellow with chemical yields of 94.27% and melting point of 165oC. Fluorescence spectroscopy measurement of compound 1 emits fluorescence with a wavelength of 546 nm which is consistent with the green color. Mass spectroscopy (ESI-MS) measurement of this compound shows m/z peak 317.1292 (ESI+). Infrared spectroscopy measurement revealed C=N vibration wavenumber at 1612.7 cm-1 which is confirmed by the result of the 1H NMR measurement that shows N=C-H chemical shift at 8.89 ppm and 13C NMR for imine carbon at 165.68 ppm. Compound 2, (2E,2'E)-2,2'-(1E,1'E)-(1,2-phenylenebis(azan-1-yl-1-ylidene))bis(methan-1-yl-1-ylidene)bis(2,1-phenylene)bis(3-phenylacrylate), is the product of esterification reaction between compound 1 and cinnamic acid that was synthesized using the Knoevenagel method. The cinnamic acid crystal is white powder that has melting point of 130oC. The crystal of compound 2 is darkish red with chemical yields of 22.26% and melting point range of 170-175oC. Fluorescence spectroscopy measurement of compound 2 emits fluorescence at three different wavelength that is at 517, 570 and 675 nm, which is consistent with the green, yellow, and red color, respectively. Infrared spectroscopy measurement of compound 2 revealed C=N vibration wavenumber at 1613.3 cm-1, C=C alkene vibration at 1453.1 cm-1, and C-O ester vibration at 1213.5 cm-1 which is confirmed by the result of the 1H NMR measurement that shows N=C-H chemical shift at 9.90 ppm and 13C NMR for imine carbon at 170.22 ppm.